2009
DOI: 10.1111/j.1834-7819.2008.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Static bone cavity in the condylar neck and mandibular notch of the mandible

Abstract: This study presents the radiographic findings of two cases of static bone cavity in the inferior aspect of the condylar neck and mandibular notch of the mandible. On plain CT, a soft tissue mass was observed in each cavity. The submandibular gland and the other glands were not found in each cavity. On contrast-enhanced CT, the soft tissue in the cavity in the inferior aspect of the condylar neck had marked linear enhancement and dilated vasculature structure was observed in the cavity. On the contrast-enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…Other tissues such as connective tissue, fat, lymphatic, muscular or vascular tissues have been found in the bone cavity and empty cavities have also been detected surgically or by advanced imaging methods (2, 3, 5, 7-9, 11). The salivary gland and fat tissue contents of the cavities in two of the presented cases are in accordance with the literature (5,12,19).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Other tissues such as connective tissue, fat, lymphatic, muscular or vascular tissues have been found in the bone cavity and empty cavities have also been detected surgically or by advanced imaging methods (2, 3, 5, 7-9, 11). The salivary gland and fat tissue contents of the cavities in two of the presented cases are in accordance with the literature (5,12,19).…”
Section: Discussionsupporting
confidence: 77%
“…The terms that have been used to describe this entity are Stafne bone defect, Stafne cyst, static bone cavity, static bone defect, lingual mandibular bony defect, and lingual mandibular salivary gland defect (2,3,5,6,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not suggest any possible cause for the ischaemia. In recent times, Minowa et al 7,8,22 suggested that bone erosion due to an acquired vascular lesion is another possible explanation for the formation of SBD of the mandible. According to them, the facial artery and its branches can become tortuous owing to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Some defects, however, have been found to be empty, possibly having been dislodged during surgery (Branstetter et al ., ; Quesada‐Gómez et al ., ; Shimizu et al ., ). These findings, as a result, have lead some researchers to conclude that Stafne's defects develop in one of four ways: (1) during embryonic development resulting in entrapped or aberrant salivary gland tissue; (2) pressure erosion by the facial artery; (3) as a result of enlargement of adjacent soft tissues, predominantly the submandibular salivary gland (Mann, ); or (4) localized failure of ossification of the mandible (Stafne, ; Campos et al ., ; Minowa et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…(3) as a result of enlargement of adjacent soft tissues, predominantly the submandibular salivary gland (Mann, 2001); or (4) localized failure of ossification of the mandible (Stafne, 1942;Campos et al, 2004;Minowa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%